An epigenetic clock for gestational age at birth based on blood methylation data. Issue 1 (December 2016) - Knight, Anna; Craig, Jeffrey; Theda, Christiane; Bækvad-Hansen, Marie; Bybjerg-Grauholm, Jonas; Hansen, Christine; Hollegaard, Mads; Hougaard, David; Mortensen, Preben; Weinsheimer, Shantel; Werge, Thomas; Brennan, Patricia; et al.
Abstract Background Gestational age is often used as a proxy for developmental maturity by clinicians and researchers alike. DNA methylation has previously been shown to be associated with age and has been used to accurately estimate chronological age in children and adults. In the current study, we examine whether DNA methylation in cord blood can be used to estimate gestational age at birth. Results We find that gestational age can be accurately estimated from DNA methylation of neonatal cord blood and blood spot samples. We calculate a DNA methylation gestational age using 148 CpG sites selected through elastic net regression in six training datasets. We evaluate predictive accuracy in nine testing datasets and find that the accuracy of the DNA methylation gestational age is consistent with that of gestational age estimates based on established methods, such as ultrasound. We also find that an increased DNA methylation gestational age relative to clinical gestational age is associated with birthweight independent of gestational age, sex, and ancestry. Conclusions DNA methylation can be used to accurately estimate gestational age at or near birth and may provide additional information relevant to developmental stage. Further studies of this predictor are warranted to determine its utility in clinical settings and for research purposes. When clinical estimates are available this measure may increase accuracy in the testing of hypotheses related to developmental age and other early life circumstances.